Investigation on effect of cold soaking on the properties of nanoclay-GFRP composite. (31st October 2018) - Kini, U Achutha; Shettar, Manjunath; Sharma, Sathyashankara; Hiremath, Pavan; Gowrishankar, M C
Abstract: In this study, nanocomposites are prepared by adding nanoclay as direct reinforcement (NCD) and nanoclay as filler material (NCF) to Glass Fiber Reinforced Polymer (GFRP). NCDs are prepared by direct casting technique and NCFs are prepared by hand lay-up technique. GFRP composites are prepared by varying nanoclay (0, 2 and 4 wt%) and glass fiber (40, 50 and 60 wt%). Specimens are immersed in water for 70 days to investigate the effect of cold soaking. Cold soaking has adverse influence on the tensile and flexural strengths of both NCD and NCF. Moisture uptake reduced with increase in weight percentage of nanoclay and glass fiber. Addition of 2 and 4 wt% of nanoclay reduces the maximum moisture uptake by 4 and 8% in NCF and 6 and 11% in NCD, respectively. Tensile and flexural strengths of cold soaked NCD decreased by 13.9 to 25% and 13.2 to 23.7% respectively. Tensile and flexural strengths of cold soaked NCF decreased by 8 to 20% and 10 to 15% respectively.